Information System Supply Chain Management with FIFO Pertetual Method - Kusumo, Haryo; Rakasiwi, Sindhu (Universitas PGRI Semarang, 2021)
Inventory is one of the assets that has an important role for the activities of a company. Problems that often occur in inventory are at the time of recording and evaluating inventory. Generally, the recording is not detailed or even manual, thus making inventory reports unclear and not good. . This study applies an information system using Supply Chain Management (SCM) at PT. Von Mustika sejahtera, a company engaged in the distributor and retail of ornamental plants in the form of orchids. This system is built using the PHP programming language and MySQL database. This study resulted in an Accounting Information System using the FIFO Pertetual method which functions for inventory management and report presentation more effectively and efficiently.